Static Seeding and Clustering of LSTM Embeddings to Learn From Loosely Time-Decoupled Events - Manasseh, Christian G.; Veliche, Razvan; Bennett, Jared; Clouse, Hamilton Scott (IEEE access, 2023)
Humans learn from the occurrence of events at different places and times to predict similar trajectories of events. We define loosely decoupled time (LDT) phenomena as two or more events that could occur in different places and across different timelines but share similarities in the nature of the event and the properties of the location. In this work, we improve the use of recurrent neural networks (RNN), particularly long short-term memory (LSTM) networks, to enable AI solutions that generate better time series predictions for LDT. We used similarity measures between the time series based on the time series properties detected by the LSTM and introduced embeddings representing these properties. The embeddings represent the properties of the event, which, coupled with the LSTM structure, can be clustered to identify similar temporally unaligned events. In this study, we explore methods of seeding a multivariate LSTM from time-invariant data related to the geophysical and demographic phenomena modeled by the LSTM. We applied these methods to time-series data derived from COVID-19 detected infection and death cases. We use publicly available socioeconomic data to seed the LSTM models, creating embeddings, to determine whether such seeding improves case predictions. The embeddings produced by these LSTMs are clustered to identify the best-matching candidates for forecasting evolving time series. Applying this method, we showed an improvement in the 10-day moving average predictions of disease propagation at the US County level.